Adapted Pedagogical Strategies in Teaching English to Young Learners with Hearing Impairment - Intan Sri Wardani; Lusi Nurhayati (Universitas Negeri Surabaya, 2026)
Teaching English to young learners with hearing impairment requires instructional approaches. The various strategies can be adapted in the process of teaching learning process. This article aims to explore on the professional teacher strategies in teaching English to young learners with hearing impairment. The method used is qualitative case study by using interview, observation and document analysis in data collected. The findings indicate that total communicative approach is an appropriate strategy for communicating with the learners. Moreover, the teacher’s creativity and professional training also included as a part of the teacher’s improvement. However, in the process of implementation the teacher faces several challenges included the internal and external challenges. Therefore, the collaboration from many stake holders is essential to maximize the targeted learning outcome. This article is expected to provide in-depth information to the readers in developing the strategies for teaching English to young learners with hearing impairment.